Effects of Nrf2 silencing on oxidative stress‐associated intestinal carcinogenesis in mice. (21st February 2016) - Yokoo, Yuh; Kijima, Aki; Ishii, Yuji; Takasu, Shinji; Tsuchiya, Takuma; Umemura, Takashi
Abstract: To assess the risk of colorectal cancer in humans with inactivation of NRF2, Nrf2 ‐proficient ( Nrf2 +/+ ) and ‐deficient ( Nrf2 −/− ) mice were exposed to potassium bromate (KBrO3 ) at concentrations of 750 or 1500 ppm for 52 weeks. Neoplastic proliferative lesions were observed in the small intestine and exhibited accumulations of β ‐catenin and cyclin D1. The lesions had characteristics similar to those in experimental models of human hereditary colorectal cancer. An additional 13‐week study was performed to examine the role of Nrf2 in the effects of oxidative stress. Significant increase in combined incidences of preneoplastic and neoplastic lesions in Nrf2 − / − mice administered high‐dose KBrO3 . In the short‐term study, although 8‐hydroxydeoxyguanosine (8‐OHdG) levels in the epithelial DNA of Nrf2 −/− mice at the high dose were significantly lower than those of the corresponding Nrf2 +/+ mice, the difference was very small. mRNA levels of Nrf2‐regulated genes were increased in Nrf2 +/+ mice. Overexpression of cyclooxygenase 2 (COX2) and increased numbers of proliferating cell nuclear antigen (PCNA)‐positive cells in the jejunal crypts were observed in Nrf2 − / − mice administered high‐dose KBrO3 . Overall, these data suggested that individuals having single‐nucleotide polymorphisms in NRF2 may have a risk of colorectal cancer to some extent. Abstract : Nrf2 deficiency increased susceptibility to oxidative stress‐induced small intestinal carcinogenesis in mice, in which COX2 overexpression followed by cell‐cycle progression was involved. Individuals having single‐nucleotide polymorphisms in NRF2 may have a risk of colorectal cancer to some extent.